(untitled) (CIPEEX, 2026)
This study analyzes the international expansion of franchising from a legal perspective, addressing both the historical aspects and the current challenges faced by this business model in Brazil. Since its consolidation in the country with pioneering chains such as CCAA and O Boticário, business franchising has proven to be an efficient alternative for entrepreneurs and investors. However, globalization has intensified the need to understand not only the internal workings of franchising but also the effects of internationalization, which involves international contracts, jurisdictional conflicts, and adaptation to foreign legislation. Thus, the research seeks to answer whether the Brazilian regulatory framework, combined with international conventions and business practices, is sufficient to guarantee legal protection and security in the relationships between franchisors and franchisees. To this end, the specific legislation (Law No. 13,966/2019) will be explored, as well as constitutional principles such as national sovereignty, free enterprise, and free competition, in addition to the role of the Brazilian Academy of Franchisees (ABF) as the sector’s representative entity.